Proceedings of PIANC Smart Rivers 2022 Green Waterways and Sustainable Navigations - Li, Yun; Hu, Yaan; Rigo, Philippe; Lefler, Francisco Esteban; Zhao, Gensheng (Lecture Notes in Civil Engineering,, 2023)
This book is a compilation of selected papers from the 10th PIANC Smart Rivers Conference (Smart Rivers 2022). The work focuses on novel techniques for inland waterways and navigation structures. The contents make valuable contributions to academic researchers, engineers in the industry, and regulators of aviation authorities. As well, readers will encounter new ideas for realizing Green Waterways and Sustainable Navigations. This is an open access book. .